On the uniqueness of an element of the best L_1-approximation for functions with values in a banach space - Babenko, V. F.; Gorbenko, M. E. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We study the problem of uniqueness of an element of the best L_1-approximation for continuous functions with values in a Banach space. We prove two theorems that characterize the uniqueness subspaces in terms of certain sets of test functions.